Comparison of the clinical efficacy of cold snare polypectomy using a thin-wire snare and thick-wire snare for small colorectal polyps - Hong Jin Yoon; Yunho Jung; Young Sin Cho; Il-Kwun Chung (Society of Gastrointestinal Intervention, 2023)
Background: Cold snare polypectomy (CSP) is an established technique for resecting small colorectal polyps without electrical current. This study aimed to compare the clinical effectiveness of thin-wire mini-snares and thick-wire mini-snares during CSP for small colorectal polyps. Methods: We prospectively enrolled 120 patients with colon polyps (5-8 mm in diameter) who underwent CSP between July and December 2017. Patients were randomly divided into two groups (thick-snare and thin-snare) according to the thickness of the snares. The complete resection rate (CRR), polyp characteristics, technical factors, and histopathologic features of resected specimens were carefully analysed. Results: In total, 137 eligible polyps were successfully resected using CSP (thin-snare group: n = 66, thick-snare group: n = 71). The location, size, morphology, and histologic findings of the polyps did not show statistically significant differences between the two groups. The CRR (thin-snare: 77.3% vs. thick-snare: 84.5%, P = 0.068), retrieval rate (100% in both groups), and the rates of tissue fly-away (P = 0.069), containing submucosal tissue (7.6% vs. 9.9%, P = 0.637), and intraprocedural or delayed polypectomy bleeding were not significantly different between the two groups. The CRR was significantly lower in sessile serrated lesions than in adenomas (odds ratio, 0.1; 95% confidence interval, 0.12-0.57; P = 0.010). Conclusion: In conclusion, when performing CSP for small polyps, the snare thickness does not seem to have a significant effect on the clinical outcomes, including CRR and the occurrence of complications.